The Influence of Pruning Shoot Age on the Growth of Hopea odorata Roxb. Cutting - Nurmawati Siregar; Kurniawati Purwaka Putri (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
Propagation of Hopea odorata Roxb. could be carried out through the vegetative methods by cuttings. Material cuttings with a high juvenility are obtained by pruning a stock plant. Information on shoot age after pruning as material cuttings were still limited. The purpose of this study was to determine the effect of shoot age after pruning on the successful propagation of H. odorata cuttings. The study design was a randomized block design with shoot age treatments of 3, 4, 5 and 6 months. Each treatment was placed in 5 blocks and each treatment consisted of 20 cuttings. Growth response of cuttings observed was cutting survival percentage, shoot height, root length, root dry weight, shoot dry weight, carbon, and nitrogen content. The results showed that the age of pruning shoots had a significant effect on all measured growth response of cuttings. H. odorata cuttings from orthotropic shoots aged 4 and 5 months after pruning showed cutting survival percentage, shoot height, root length, shoot and root dry weight were higher than shoots aged 3 and 6 months after pruning. The age of 6 months pruning shoots showed the highest C/N ratio (18.14) and carbon content (47.48 percent), but but the lowest nitrogen content (2.62 percent). The percentage of woody on shoots aged 4 and 5 months after pruning was 50%, while almost all of the cuttings on shoots of the age of 6 months were woody. The best propagation material for H. odorata cuttings was orthotropic shoots aged 5 months after pruning, because of the high cuttings survival percentage (94.18 percent). In addition C/N ratio from shoot aged 5 months (15,11) was higher than from shoot aged 4 months (13,14).